ESTABLISHMENT AND ASSISTANCE OF INDEPENDENT CARE FOR THE USE OF FAMILY MEDICINAL PLANTS FOR SOCIETY - Kurniawan, K; Istiqomah, Solikah Ana; Budi Sawitri, Satwika (PC IAI Sragen, 2023)
Health Effort Based Human Resources is a real fact of community participated in health development that can trigger the community empowerment activities, such as Family Medicinal Plants (FMP). FMP are several kinds of selection plants that could be planted in the yard or home environment. The existence of this plants in the home yard are important, especially for the family with lack of access to the health services. This was a community service; community empowerment entitled “Establishment and Assistance for Independent Care for the Use of Family Medicinal Plants (TOGA) in the Community